Evaluation of fungicidal action of four products on external fungal biota of grains. - Alvarez, Estefanía; Cardoso, Marcelo Leandro; Bartosik, Ricardo Enrique; Castellari, Claudia Carla; De La Torre, Diego; Erreguerena, Ignacio Antonio; Abadia, María Bernadette (University of Manitoba, Canadá, 2021)
Corn, the main crop in Argentina, is normally harvested and stored in silo bags above the safe storage moisture content for 3-6 months, and faces high risk of quality losses. The evaluation of fungicidal/fungistatic products that could potentially be used to protect wet grain stored in silo bags, has not been widely studied. Thus, the objective of this study was to make a preliminary in-vitro comparative evaluation of four different fungicidal treatments in corn: 1) propionic acid (3 L/t); 2) a quaternary ammonium compound (3 L/t, diluted 1:25 with water); 3) sulfur dioxide (initial dose: 15% v/v); 4) phosphine (initial dose: 6.6 g/m3) along with their respective controls (non-treated). In treatments 1 and 2 (liquids) corn was sprayed with the product and then stored in a sterilized glass jar. In treatment 3, sulfur dioxide was injected into a previously sealed glass jar. In treatment 4, glass jars were placed inside a plastic drum of 60 L capacity with two aluminum phosphide tablets (0.2 g phosphine each) and closed. Both liquids and the phosphine treatments had an exposure time of 15 d (at 25 ± 1°C), while in the sulfur dioxide treatment, three exposure times were evaluated (5 min, 5 and 24 h, all at the same temperature). After the various treatments, the fungal biota (molds and yeasts) was evaluated. The results showed that the propionic acid treatment achieved a total control of fungal biota. Treatment with sulfur dioxide showed a reduction of 2-3 log10 (CFU/g DM) compared to non-treated samples. Finally, the quaternary ammonium compound and phosphine treatments only achieved a reduction in the number of colonies of 1 log10 (CFU/g DM). Based on the results of this study, propionic acid seems to be a good solution for improving the storability of wet corn in silo bags. Nevertheless, more information should be generated at laboratory and full scales.